Come hell or high water : the Territory rock opera - Sharp, Bob, 1953-; Foran, B. D. (Barney D.); Arts Council of Australia. Northern Territory Division (Paddington, N.S.W. : Currency Press in association with Northern Territory Arts Council, 1988)
Rock opera, European and Aboriginal Australians fighting for their place on the land; central Australia; musical play.
Keywords: Musicals -- Librettos; Music; Northern Territory - Central NT